Gender Affirming Body Contouring and Physical Transformation in Transgender Individuals - Arjun Asokan; Madhu K. Sudheendran (Indian Journal of Plastic Surgery)
There is a subset of transgender individuals, who after having undergone gender affirming surgeries want body contouring so that the overall body shape is congruent to the body image. Hormonal therapy can bring about a considerable change in the physical transformation. However, there is an increase in requests for specific body contouring procedures because of increased awareness in the society. There are significant differences between the skeletal as well as soft tissue characteristics of male and female body. Body contouring in transgender individuals can be achieved by altering the skeletal structure or the overlying soft tissues or combining both. In this article, we discuss body contouring as an adjunct to gender affirming surgeries, in both male to female and female to male transgender individuals.